The Effect of Green Intellectual Capital, Green Accounting, and Carbon Emission Disclosure on Enterprise Value: The Moderating Role of Managerial Ownership - Davita Dewardani; I Gusti Ketut Agung Ulupui; Ayatulloh Michael Musyaffi (Review of Ethics in Sustainable Finance and Accounting, 2025)
This study seeks to examine the influence of green intellectual capital (GIC), green accounting (GA), and carbon emission disclosure (CED) on financial performance, as proxied by enterprise value (EV), whilst also evaluating the moderating role of managerial ownership in mining sector companies listed on the Indonesia Stock Exchange over the 2020–2024 period. A quantitative approach was employed, with secondary data gathered from corporate financial statements and annual reports. Through purposive sampling, a total of 58 companies were selected, yielding 290 observations in aggregate. Data analysis was done by multiple linear regression and Moderated Regression Analysis (MRA) with IBM SPSS 26. The findings reveal that green intellectual capital and green accounting exert a negative and significant effect on enterprise value, whereas carbon emission disclosure was found to bear a positive and significant impact on enterprise value. Managerial ownership was similarly determined to impose a negative and significant effect on enterprise value. As a moderating variable, managerial ownership was shown to reinforce the relationship between green accounting and enterprise value, yet proved unable to moderate the effects of either green intellectual capital or carbon emission disclosure. An Adjusted R-Square value of 0.756 suggests that 75.6 per cent of the variation in enterprise value is accounted by the variables within the research model, with the remaining portion attributed to factors beyond the model. These findings suggest that investments directed toward environmental sustainability do not invariably produce short-term economic gains; nonetheless, transparency in carbon emissions disclosure may strengthen investor confidence and enhance corporate value.